Marketing Analysis Of Lele Dumbo Fish (Clarias Gariepinus) In Mojomulyo Village, Puger Distict - Teguh Hari Santosa; Wilda Alfi Kurniasari; Saptya Prawitasari (Universitas Muhammadiyah Jember, 2020)
Catfish is a freshwater fish that has economic value. One of the centers of African catfish farming was in the Village of Mojomulyo, District of Puger. This purpose of this study were: find out how many types of marketing channels of African catfish, the tasks and functions of the marketing institutions involved, analyze the efficiency of marketing of African catfish. This research method was amethod descriptive and survey with the location chosen deliberately, namely in the Village of Mojomulyo, District of Puger. Sampling was carried out using themethod Proposionate Cluster Random Sampling, respondents from marketing institutions were determined by themethod Snowball sampling. Data collection techniques using interview techniques. Data analysis uses marketing margin analysis and farmer's share. The results of the study were: there were 3 patterns of marketing channels for African catfish in Mojomulyo Village, Puger District, showing marketing channels 1 level (farmers - collectors - consumers), marketing channels 2 level (farmers - collectors - big traders - consumers) and marketing channels 3 level (farmers - collectors - wholesalers - retailers - consumers). The highest marketing efficiency of catfish in Mojomulyo Village, Subdistrict of Puger, Jember Regency was found in the marketing channel 1 level with a margin of Rp 3000 per kg and the Farmer's share highestof 82.86%. The 2-level marketing channel margin value is Rp 4,620 per kg with a Farmer's share value of 75.95%, while the lowest marketing efficiency was in the 3-level marketing channel with the highest margin value of Rp9,265 per kg and the Farmer's share lowestof 60.14%. The marketing of catfish in Mojomulyo Village, subdistrict of Puger was efficient, because farmer’s share of 1 level, 2 level and 3 level of marketing channel was more than 50%.